How Deep Learning Pedagogy Shapes Character Education in Indonesian Madrasahs - Mohammad Fitri; Wahyuningsih; Kartini Rahman Nisa (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2026)
This study investigates the implementation of deep learning as a transformative approach for integrating academic achievement and character formation in madrasahs in Sikka Regency, Indonesia. Using a qualitative descriptive design, data was collected through interviews with teachers, students, and school leaders, classroom observations, and document analysis. The findings reveal that deep learning is perceived by teachers as a holistic pedagogical approach that integrates cognitive, affective, and socio-emotional dimensions, while students experience it implicitly through more engaging and meaningful learning activities. Character internalization occurs through structured habituation, teacher modeling, and contextual learning tasks, including daily religious practices, differentiated instruction, and experiential learning such as market observation. These practices reflect the principles of mindful, meaningful, and joyful learning, aligned with Kurikulum Merdeka. The study also identifies challenges such as limited infrastructure, varying teacher readiness, and socio-economic constraints of students, while highlighting institutional efforts in teacher training and digital resource provision. Theoretically, the findings align with the perspectives of Hattie on visible learning, OECD on 21st-century competencies, and Fullan on systemic educational change. Overall, deep learning in madrasahs functions not only as a pedagogical strategy but also as an ecosystem for holistic character development.